CORRELATION OF INFLAMMATION BIOMARKERS WITH THE TRADITIONAL RISK FACTORS IN PATIENTS WITH ACUTE CORONARY SYNDROME - I. S. Skopec; N. N. Vezikova; I. M. Marusenko; O. Yu. Barysheva; A. V. Malafeev; A. N. Malygin (Столичная издательская компания, 2016)
Actuality of cardiovascular diseases today determines the high interest to study pathogenesis of atherosclerosis and to searching new risk factors which could help to optimize primary and secondary prevention. Study the correlation between biomarkers of inflammation and traditional risk factors (TRF) in patients with different forms of ischemic heart disease is really important today.Aim. To determine the correlation between TRF and the level of biomarkers of the inflammation and endothelial dysfunction in patients with acute coronary syndrome (ACS). Material and methods. Patients (n=62) aged from 24 to 50 years (mean age 43.98±4.73), who were admitted to the hospital due to ACS, were included into the study. Correlations between TRF and the levels of biomarkers of the inflammation and endothelial dysfunction were assessed. The following biomarkers levels were determined: high-sensitivity C-reactive protein (hsCRP), homocysteine, soluble vascular cell (sVCAM-1) and intracellular (sICAM-1) adhesion molecule type 1, soluble E-selectin (sE-selectin), nitrate, neopterin, matrix metalloproteinase type 3 (MMP-3).Results. TRF, including modifiable ones, were often revealed in patients of the studied group. Some correlations between TRF and high concentrations of inflammatory biomarkers were determined. Patients with the family history of early cardiovascular diseases had higher concentration of sVCAM-1 (1047.78±516.98 ng/ml) in comparison with the patients without this TRF (705.57±239.28 ng/ml), p=0.017. Patients with arterial hypertension had higher level of MMP-3 (9.31±3.63 ng/ml) versus patients without hypertension (5.02±3.66 ng/ml), р=0.011). Patients with abdominal obesity compared with patients without this TRF demonstrated higher concentration of nitrate in acute (208.45±91.85 ng/ml vs 154.53 ng/ml, р=0.028) and long-term (193.53±40.02 ng/ml vs 173.48 ng/ml, р=0.028) periods of ASC.Conclusion. The study showed the significant correlation between ТRF and high levels of some biomarkers of inflammation and endothelial dysfunctions in patients with ACS. So it is probably associated with more rapid progression of the atherosclerosis, higher risk of atherothrombotic events, complicated course of ischemic heart disease and unfavorable outcomes.